Analisis Syariah Marketing Mix Arrum BPKB dan Urgensinya dalam Meningkatkan Pendapatan UMKM Nasabah Pegadaian UPS Diponegoro Sumenep - Munawaroh, Sayyidatul; Makhtum, Ahmad (J-MAS (Jurnal Manajemen dan Sains), 2024)
The main objective of this study is to analyse the impact of the Arrum BPKB sharia marketing mix at Pegadaian UPS Diponegoro on the income level of MSME customers.This qualitative case study uses structured interviews to collect primary data from MSME players, complemented by secondary data from institutional records. The focus of the analysis is placed on understanding how the application of Sharia principles in marketing can improve business funding solutions. The application of Sharia Marketing Mix for Arrum BPKB financing has significantly increased customer interest and participation. Interviews with five MSME customers showed a marked increase in their daily and monthly income, confirming the effectiveness of this strategy in the real world. This study highlights the alignment of Shariah-compliant practices with customer needs and market dynamics. The findings underscore the importance of incorporating Shariah principles in marketing strategies in Islamic financial services. In practical terms, this approach not only helps in complying with ethical standards, but also enhances customer trust and financial inclusion for cash-strapped MSMEs. This study introduces new insights into the localised impact of Shariah marketing practices on MSME profitability, particularly in the Indonesian financial services context, and sets a precedent for further regional studies